Effect of thermal treatment on solid-solid interface of hematite thin film synthesized by spin-coating deposition solution - Bellido-Aguilar, Daniel Angel; Tofanello, Aryane; Souza, Flavio L.; Furini, Leonardo Negri [UNESP]; Constantino, Carlos José Leopoldo [UNESP] (Elsevier, 2016)
This work describes hematite films prepared by a spin-coating deposition solution (SCDS) method that is a sol-gel method derived technique. Hematite films were prepared at two heat treatment temperatures (500 °C and 800 °C) and the influence of thermal treatment on the photoelectrochemical performance was studied. In addition, since the SCDS method allows an optimal control of stoichiometry and impurity incorporation, hematite films modified with Zn2 + and Sn4 + were also prepared. The 800 °C-treated hematite films had a higher wettability and roughness that enabled them to have a better photocatalytic response in comparison with that of 500 °C-treated hematite films. Moreover, modified hematite films demonstrated to have a performance slightly better than that of undoped hematite film as shown in linear sweep voltammetry and chronoamperometry results. Although an improvement in the performance of hematite films was achieved by annealing at higher temperatures and incorporating Zn2 + or Sn4 +, the general photocatalytic response of the films was poor. Two plausible hypotheses were discussed related to the (i) dopant segregation at grain boundary, and (ii) poor contact between the hematite and fluorine doped tin oxide layer (from the glass substrate), which was experimentally confirmed by a cross-sectional analysis conducted using scanning electron microscopy (SEM). In fact, additional experiments need to be done in order to improve the hematite deposition and make the SCDS a promise method for industrial application.
Keywords: Doping; Iron oxide; Nanostructure; Thin film